Uwagi na temat programu reformy ubezpieczeń społecznych w Polsce - Piotrowski, Włodzimierz (Wydział Prawa i Administracji UAM, 1995)
The author agrees that the social security system in Poland needs to be reformed. However, he disagrees with certain aspects of the draft proposal of the reforms presented by the government. Not only social insurance system but the whole social care and security system must be reformed. The insurance programme referred to in the paper does not include health insurance, unemployment insurance and insurance against employer's insolvency. The author fully agrees with the attempt to restore benefits paid during the illness of the employee, disability benefits or pensions paid to the elderly, or the family benefits. However, the author disagrees with the proposal included in the draft to maintain social security benefits at the level of social support benefits. Although the role of the state in the area of social care should be limited, other types of benefits, an retirement benefits in particular, must not be lowered to the level of social care benefits paid to the poorest. As far as some more detailed questions are concerned, the author postulates a more radical change in the accident insurance which may and should also have a preventive function. For that, however, it would be necessary to implements far more reaching changes in the structures which provide that type of insurance than the ones proposed in the draft.
Some comments on the reforms of the social security system in Poland